Social Innovation and Networks in Rural Territories: the case of EPAM - Ferreiro, Maria de Fátima; Sousa, C. (European Conference on Innovation and Entrepreneurship, 2018)
The paper presents a case study related to the production of aromatic and medicinal herbs in rural territories within a conceptual and methodological framework focused on social innovation and networks. These concepts present interesting potentialities in the discussion of the challenges and design of solutions to overcome the main problems of rural territories (e.g. desertification, ageing, unemployment, climatic changes). The linkage between social innovation and territorial development has been developed in the literature (Estensoro, 2015; CRISES, 2003; 2016; Bellemare & Klein, 2010; MacCAllum et al, 2009). But extant research focus mainly on urban territories and, therefore, there is a gap in the analysis of social innovation in rural territories, their specific problems and challenges (Ferreiro & Sousa, 2017). Social innovation in the context of territorial development is considered a “‘transformer’ of spatial relations” (MacCAllum et al, 2009, p.12). Territorially speaking social innovation takes place also with the transformation of place-based social relations improving governance and decision-making forums, but also “the reproduction of place-bound and spatially exchanged identities and culture. […]. Social innovation is quite often either locally or regionally specific, or/and spatially negotiated between agents and institutions that have a strong territorial affiliation” (Idem, ibidem). The concept of social innovation and the methodology of social network analysis will be applied to the case study of EPAM, a project started in 2011 aiming the promotion of development of medicinal and aromatic herbs. The EPAM project is led by ADCMoura, a Portuguese Association of Local Development located in a very low-density region - Baixo Alentejo. EPAM is presented as a social innovation envisaging economic and rural development across several European countries. Networking, research, dissemination, and training, constitute the tasks of a ‘collaborative methodology’ and a ‘strategic and innovative platform’. The project establishes a network of collaboration between different sectors and actors (public, private and non-profit) in the value-chain of aromatic and medicinal herbs. These networks conveys and promotes social capital. The paper uses the case to critically discuss: i) the role of social innovation in the development of rural territories; ii) the network arising from the project and its importance to rural development.